Internal emotional factors as stress protection strategies in future teachers - Gavín Chocano, Óscar; García-Martínez, Inmaculada; Pérez-Navío, Eufrasio; Quijano-López, Rocío (Revista Complutense de Educación, 2024)
INTRODUCTION. The subjective well-being of the person varies in the complementarity between emotional and cognitive components, with substantial implications for the overall development of each individual. Therefore, identifying those socioemotional protection factors will allow us to define regulatory strategies against stress. The present study aims to provide evidence on the value of Emotional Intelligence and Resilience as protective factors against stress, with Self-Esteem acting as a mediating variable, by using the partial least squares approach (PLS-SEM) path model. METHOD. A total of 723 university students participated, 588 were women (81.30%) and 135 men (18.70%), with an average age of 21.43 years (±5.65). The following instruments were used: Resilience Scale (RS-14), Wong Law Emotional Intelligence Scale (WLEIS-S), Rosenberg Self-Esteem Scale (RSE), Satisfaction with Life Scale (SWLS) and Perceived Stress Scale (PSS-10). RESULTS. The results evidenced the relationship between the dimensions of the instruments considered, with self-esteem acting as an empowering variable, the coefficients of determination are: self-esteem (r²=.632), life satisfaction (r²=.313), and perceived stress (r²=.509), with a root mean square error (SRMR) of .067. DISCUSSION. The practical consequences underline the need to promote useful educational strategies for analysing emotional situations.